2019
DOI: 10.1139/cjpp-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-seryl-aspartyl-lysyl-proline treatment protects heart against excessive myocardial injury and heart failure in mice

Abstract: Myocardial infarction (MI) in mice results in cardiac rupture at 4–7 days after MI, whereas cardiac fibrosis and dysfunction occur later. N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) has anti-inflammatory, anti-fibrotic, and pro-angiogenic properties. We hypothesized that Ac-SDKP reduces cardiac rupture and adverse cardiac remodeling, and improves function by promoting angiogenesis and inhibiting detrimental reactive fibrosis and inflammation after MI. C57BL/6J mice were subjected to MI and treated with Ac-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…We have also reported that T4, at a dose that is unable to generate optimal circulating Ac-SDKP concentrations (Rhaleb et al 2001 b ), prevents cardiac rupture and improves cardiac function post-myocardial infarction (MI) via its anti-inflammatory, proangiogenic, and anti-apoptotic actions in a murine model of acute MI (Peng et al 2014). Comparable results are obtained when Ac-SDKP was used instead of Tβ4 (Peng et al 2019, in press). The MI model in rodents shares both clinical and pathological features of post-MI with changes found in human hearts, including cardiac rupture and dysfunction (Bock-Marquette et al 2004).…”
Section: General Aspects Of Thymosin β4 (Tβ4)–n-acetylseryl-aspartyl-mentioning
confidence: 85%
“…We have also reported that T4, at a dose that is unable to generate optimal circulating Ac-SDKP concentrations (Rhaleb et al 2001 b ), prevents cardiac rupture and improves cardiac function post-myocardial infarction (MI) via its anti-inflammatory, proangiogenic, and anti-apoptotic actions in a murine model of acute MI (Peng et al 2014). Comparable results are obtained when Ac-SDKP was used instead of Tβ4 (Peng et al 2019, in press). The MI model in rodents shares both clinical and pathological features of post-MI with changes found in human hearts, including cardiac rupture and dysfunction (Bock-Marquette et al 2004).…”
Section: General Aspects Of Thymosin β4 (Tβ4)–n-acetylseryl-aspartyl-mentioning
confidence: 85%
“…TCM is widely applied in the prophylaxis and therapy of HF [24]. LGZGD, as one of the widely used TCM, can effectively regulate the cardiac function and structure in HF by ameliorating the microstructural remodeling, reducing the myocardial inflammation injury and myocardial fibrosis [9,10,[25][26][27], and can protect myocardial cells by inhibiting apoptosis of H9c2 cells [12]. As one of the active components of LGZGD, previous studies show that ATL-III has a protective effect on myocardial cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent and severe ERS induces myocardial cell apoptosis, which is one mechanism responsible for the pathogenesis of HF [ 7 , 8 ]. As a result, suppression of ERS could be a major concern for HF [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of literature has shown that C/EBPζ is involved in cardiomyocyte apoptosis, cardiac hypertrophy, and heart fibrosis. Various stimuli such as TAC, myocardial infraction (MI), and diabetes activate ER stress by increasing C/EBPζ expression in myocardial fibrosis [308][309][310]. In addition, C/EBPζ knockout mice display decreased cardiomyocyte apoptosis and subdued cardiac fibrosis under TAC, ischemia-reperfusion (I/R) injury, and Ang II-induced hypertension compared to wild-type mice [311][312][313].…”
Section: C/mentioning
confidence: 99%